Effect of Croton caudatus Geiseler Aqueous Root Extract on Reproductive and Biochemical Parameters in Male Wistar Rats - Razif Dasiman; Mastura Abd Malek; Ebby Anuar Bahari; Fatin Nadzirah Zakaria; Nina Keterina Hashim; Afiqah Samsuddin; Kamalru Azman Daud; Fatimah Sham; Zulkhairi Amom (The Prodia Education and Research Institute (PERI), 2020)
BACKGROUND: Croton caudatus Geiseler (CCG), a local herb that empirically has been used as traditional medicine for malaria, fever, convulsions, and rheumatic arthritis. This study aimed to investigate the effect of CCG on reproductive and biochemical parameters in male Wistar rats.METHODS: Twenty-four Wistar male rats were divided randomly into four groups, which were treated with CCG aqueous root extract at the concentration of 0-16 mg/kg, via oral gavage. After 21 days of treatment, blood, sperm, and testes were harvested for analyses. Sperm parameters were evaluated using computer-assisted sperm analyser (Hamilton Thorne Sperm Analyzer), and morphometric analyses of histological changes were performed.RESULTS: CCG extract at 8 and 16 mg/kg significantly (p<0.05) increased the total sperm count, concentration, and motility; whereby, only 16 mg/kg significantly decreased the percentage of abnormal sperm morphology. Testosterone hormones levels were the highest in 4 mg/kg CCG but were slightly decreased in 8 and 16 mg/kg CCG. The histological results showed a significant increase in the germinal epithelial height, decrease of lumen size at 16 mg/kg of CCG extract. No significant changes of alanine aminotransferase (ALT) and creatinine levels in serum from all CCG extract groups. However, the aspartate aminotransferase (AST) level in 8 mg/kg CCG was elevated, and the blood urea nitrogen (BUN) level was decreased in all CCG extract groups.CONCLUSION: In conclusion, the CCG extract at 4 mg/kg has the potential to enhance spermatogenesis activity within the seminiferous tubules in rats without any hepatotoxicity and nephrotoxicity effect on the liver and kidney.KEYWORDS: Croton caudatus Geiseler, rats, spermatogenesis, seminiferous tubules, testis, testosterone